Influence Communication, Work and Discipline of the education level on employee performance at PT. Fruit Oil (SBS) District. Kinali, Kab. West Pasaman - Fauzan, Fauzan; Sari, Mareta Kemala; Utami, Hayu Yolanda (Pendidikan Ekonomi, 2014)
ABSTRACT The formulation of the issues raised in this study is "The Effect of Communication And Work Discipline Against Employee Job Performance". The variables of this study are: Communication, Work Discipline and level of education (as independent variables) and Job Performance (as dependent variable). This study analyzed how much influence communication on employee performance, discipline working on employee performance and discipline of communication and work together on employee performance.This study aims to reveal (1) the influence of communication on employee performance, (2) the effect of labor discipline on employee performance, (3) the effect of educational level on employee performance (4) the effect of communication, work discipline and level of education collectively same on employee performance.This research was conducted in PT. Fruit Oil (SBS) Kec.Kinali, Kab. Pasaman West. The population in this study amounted to 92 employees. sample in this study amounted to 75 employees. This type of research is descriptive and associative data analysis technique used is descriptive analysis techniques, asumsiklasik test and multiple linear regression analysis.The results showed overall that ( 1 ) the level of communication and a significant positive effect on employee performance with communication coefficient is positive 0.414 and 3.431 tcount with significant 0.001 < 0.05, (2) labor discipline and a significant positive effect on achievement working with labor discipline coefficient is positive 0.272 and 3.748 tcount with significant 0.000 < 0.05, ( 3 ) education level but not significant positive effect on job performance with work discipline coefficient is positive 0.090 and 0.533 tcount with significant 0.596 > 0.05, ( 4 ) communication , work discipline and education levels , and a significant positive effect on job performance . Based on the results of the ANOVA test or Ftest Fhitung obtained at 882.776 with a significant level of 0.000 . Due to the significance level of 0.000 < 0.05. As for the suggestion that the writer can convey to future studies is recommended to add other independent variables besides kominikasi , work discipline and education level , which of course can affect employee performance dependent variable in order to further complement this study because there are other independent variables outside this study that might affect their job performance and look for the scope of the wider population in this study population .